2021
DOI: 10.28918/jei.v6i1.3638
|View full text |Cite
|
Sign up to set email alerts
|

A Reinforcement of Religious Understanding of High School Students on Radicalism During Pandemic

Abstract: Teroris sebagai manifestasi dari radikalisme seolah timbul dan tenggelam. Keberadaannya diam, namun suatu saat bisa muncul menyasar semua segmen. Segmen yang mudah disasar adalah remaja usia pelajar level Sekolah Menengah Atas. Hal ini karena mereka adalah pridadi peralihan dari masa kanak-kanak menuju dewasa. Peserta didik yang baik adalah peserta didik yang cerdas membaca fenomena alam dan fenomena sosial. Mindset positive thingking terlihat dengan kejernihan berfikir dan membawa fenomena pandemi sebagai ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…This moderate result may be attributed to their knowledge and understanding of the meaning and significance of the Holy Eucharist, the reinforcement of home, school, and local faith community, and their awareness of their spiritual responsibility while attending the online mass. This is supported by Raharjo et al [16] in their findings that the formation of habit and understanding can be possible through modeling attitudes and behaviors that are easy to imitate from teachers and peers and by optimizing the role of parents to assist students in distance learning patterns, learning from home, or online learning. Moreover, the study found a high level of participation [M = 3.92] among students attending online masses.…”
Section: The Degree Of Motivation and Level Of Participation Of Senio...mentioning
confidence: 83%
“…This moderate result may be attributed to their knowledge and understanding of the meaning and significance of the Holy Eucharist, the reinforcement of home, school, and local faith community, and their awareness of their spiritual responsibility while attending the online mass. This is supported by Raharjo et al [16] in their findings that the formation of habit and understanding can be possible through modeling attitudes and behaviors that are easy to imitate from teachers and peers and by optimizing the role of parents to assist students in distance learning patterns, learning from home, or online learning. Moreover, the study found a high level of participation [M = 3.92] among students attending online masses.…”
Section: The Degree Of Motivation and Level Of Participation Of Senio...mentioning
confidence: 83%